China–Malaysia Cross-Border Data Governance: ASEAN and Regional Legal Interactions - Deng, Shan; Ab Rahman, Rozanah; Ariffin, Mariani (Faculty of Law, Hasanuddin University, 2025)
In the context of the digital economy, cross-border data governance cooperation between China and Malaysia is constrained by two factors: differences in domestic data protection laws and the lack of coherence among existing multilateral frameworks. Prior scholarship primarily examines cross-border data governance through single-treaty frameworks, while the role of the Association of Southeast Asian Nations (ASEAN) as an institutional intermediary has not been systematically analysed. In particular, institutional coordination pathways between China and Malaysia remain underexplored. The study adopts a qualitative methodology, combining textual and comparative analyses, to examine the institutional structure of the ASEAN Data Governance Framework (ADGF). It investigates ASEAN’s role in coordinating the multilateral mechanisms of the Regional Comprehensive Economic Partnership (RCEP), the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), and the China–ASEAN Free Trade Agreement (CAFTA), where the institutional challenges in China–Malaysia cooperation are further analysed. The analysis shows that while ASEAN contributes to reducing institutional differences, its coordination mechanisms remain limited. The study therefore adopts ASEAN as an institutional coordination platform and develops a governance pathway that integrates bilateral and regional rules to examine institutional compatibility between China and Malaysia.